Natural gum and resin bearing species of Ethiopia and their potential applications - Tadeáe, W.=700 1 Desalegn, G.; Alia, R.
(Es, En)
ilus., 34 ref.
Keywords: ACACIA; COMMIFHORA; PLANTAS GOMIFERAS; GOMA ARABIGA; RESINAS; USOS; ETIOPIA